Meanings of Advertising in Market Communication - Vaišvilienė, Alina (Knygotyra, 2008)
[full article and abstract in Lithuanian; abstract in English]The article analyzes the concept of advertising. The author defines specific elements of advertising and relations between advertising and other communication means. The aim of the article is to define the niche of advertising in a market communication system.After the studying available scientific sources the author concludes that concept of advertising is not constant in market communication system. Inconstancy of the concept is determined by versatility of the object of research and its transdisciplinary nature. The broad area of activity, instable meaning in market communication system and different points of view to the range of advertising makes a tough issue to analyze the advertising process itself.Despite the fact that advertising production is widely seen in a context of commercial reality, the communication of advertising in a modern society is influenced not just by growing competition but also by sociocultural reasons and diverse contacts of individuals. The conclusion is reached that boundaries of advertising in market communication dissolves and parts of traditional functions of advertising are transitioned to other means of market communication.
Keywords: ...